Influences of the organizational culture on management change and faculty development in natural gases engineering education - Duşe, Dan Maniu; Duşe, Carmen (My University, 2012)
This paper sets out to present the defining elements of the cultural dimensions in a classical University in Romania (»Lucian Blaga« University in Sibiu) and their influence on change and development program of the university's management, especially on Natural Gases Engineering Education. Management change and development are considered under the umbrella of the new educational law (Law no. 1/2011) that came into force in Romania. Ideas that resulted by using the three-dimensional morphological matrix with the axes: organizational culture - organizational change - cultural intensity development are analysed and presented in five distinct hypostases of the five cultural dimensions promoted by the Dutch researcher Geert Hofstede. Expected results of the research are connected to discovering the activities that allow organizational, institutional and academic management change according to the cultural specifics and to the new national education law.
AGH Drilling, Oil, Gas
Keywords: academic management; change and faculty development; classical university; organizational culture; education law; natural gases engineering education